2023
DOI: 10.1099/ijsem.0.006138
|View full text |Cite
|
Sign up to set email alerts
|

Nocardioides cremeus sp. nov., Nocardioides abyssi sp. nov. and Nocardioides oceani sp. nov., three actinobacteria isolated from Western Pacific Ocean sediment

Wenjing Wang,
Yihan Ding,
Shiping Wei
et al.

Abstract: Three Gram-stain-positive, non-motile, short rod-shaped, catalase-positive and oxidase-negative actinomycete strains (SOB44T, SOB72T and SOB77T) were isolated from a deep-sea sediment sample collected from the Western Pacific Ocean. Cells of the three strains showed optimum growth at 30 °C and pH 7.0. Strains SOB44T, SOB72T and SOB77T could tolerate up to 10, 9 and 9 % (w/v) NaCl concentration and grow at pH 5.0–12.0, 5.0–11.0 and 5.0–11.0, respectively. Phylogenetic results based on 16S rRNA gene sequences sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A comparison growth experiment was tested on R2A agar, brain heart infusion (BHI) agar, BHI+5 % (v/v) defibrinated sheep blood agar, Luria-Bertani agar (LB), marine agar (MA), MacConkey agar (MAC), nutrient agar (NA), and tryptic soy agar (TSA), revealed that the four isolates grew best on R2A agar. Therefore, the optimal growth conditions for the four isolates were tested in R2A broth at different temperatures (4,10,15,20,25,28,30,35,37, and 42 ºC), tolerance to NaCl (0-6 %, w/v, 0.5 % intervals), and pH (pH 3.0-12.0, at 1.0 pH unit intervals), the following buffer systems were used to adjust medium pH: Na 2 HPO 4 /citric acid (pH ≤7.0), Tris/HCl (pH 8.0-9.0), and Na 2 CO 3 /NaHCO 3 (pH ≥10.0). For strains HM61 T and HM23, the optimal growth conditions were 25 °C (range, 4-37 °C), 0 % NaCl (up to 4.5 %), and pH 8.0 (range, pH 6.0-10.0), whereas S-34 T and S-58 grew optimally at 28 °C (range, 4-37 °C), 0.5 % NaCl (up to 3.5 %), and pH 7.0 (range, pH 6.0-10.0).…”
Section: Phenotypic and Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison growth experiment was tested on R2A agar, brain heart infusion (BHI) agar, BHI+5 % (v/v) defibrinated sheep blood agar, Luria-Bertani agar (LB), marine agar (MA), MacConkey agar (MAC), nutrient agar (NA), and tryptic soy agar (TSA), revealed that the four isolates grew best on R2A agar. Therefore, the optimal growth conditions for the four isolates were tested in R2A broth at different temperatures (4,10,15,20,25,28,30,35,37, and 42 ºC), tolerance to NaCl (0-6 %, w/v, 0.5 % intervals), and pH (pH 3.0-12.0, at 1.0 pH unit intervals), the following buffer systems were used to adjust medium pH: Na 2 HPO 4 /citric acid (pH ≤7.0), Tris/HCl (pH 8.0-9.0), and Na 2 CO 3 /NaHCO 3 (pH ≥10.0). For strains HM61 T and HM23, the optimal growth conditions were 25 °C (range, 4-37 °C), 0 % NaCl (up to 4.5 %), and pH 8.0 (range, pH 6.0-10.0), whereas S-34 T and S-58 grew optimally at 28 °C (range, 4-37 °C), 0.5 % NaCl (up to 3.5 %), and pH 7.0 (range, pH 6.0-10.0).…”
Section: Phenotypic and Biochemical Analysismentioning
confidence: 99%
“…The genus Nocardioides, a member of the family Nocardioidaceae within the order Propionibacteriales in the class Actinomycetes, was first described by Prauser in 1976 with Nocardioides albus as the type species [1,2]. At the time of writing, 166 species have been validly named and published in LPSN (https://lpsn.dsmz.de/genus/Nocardioides, accessed May 2024) [3], which were isolated from diverse sources, such as faeces of wild animals [4,5], soil [6,7], plants [8,9], and other environments [10][11][12][13][14]. Members of the genus Nocardioides are aerobic, Gram-stain-positive, mesophilic, pH-neutral, coccus-or rod-shaped bacteria.…”
Section: Introductionmentioning
confidence: 99%